2000
DOI: 10.3758/bf03211844
|View full text |Cite
|
Sign up to set email alerts
|

The stroop effect: It is not the robust phenomenon that you have thought it to be

Abstract: Five experiments demonstrate that context has a powerful effect on the ease with which people can name (Experiments 1-3) or categorize (Experiments 4-5) a stimulus while ignoring another stimulus, irrelevant or conflicting with the target. Selectivity of attention to the target dimension was gauged through Stroop and Garner effects, When the stimulus values along the target dimension and the to-beignored dimension were correlated over the experimental trials, large effects of Stroop and Garner influenced perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 42 publications
8
103
0
Order By: Relevance
“…Algom and colleagues pointed out that factors associated with the stimulus can produce interference or facilitation in Garner and Stroop-like paradigms (e.g., Algom et al, 1996;Dishow-Berkovits & Algom, 2000;Pansky & Algom, 1999;Pansky & Algom, 2002). For instance, Pansky and Algom (1999) demonstrated that larger Stroop effects could be observed with a manyvalued irrelevant dimension than with a binary-valued irrelevant dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Algom and colleagues pointed out that factors associated with the stimulus can produce interference or facilitation in Garner and Stroop-like paradigms (e.g., Algom et al, 1996;Dishow-Berkovits & Algom, 2000;Pansky & Algom, 1999;Pansky & Algom, 2002). For instance, Pansky and Algom (1999) demonstrated that larger Stroop effects could be observed with a manyvalued irrelevant dimension than with a binary-valued irrelevant dimension.…”
Section: Discussionmentioning
confidence: 99%
“…1B). As Mordkoff (2012) argued, increasing the proportion of congruent trials makes the irrelevant task dimension (i.e., the color word in the Stroop task) informative (see also Dishon-Berkovits & Algom, 2000). As a consequence, participants might have been encouraged to pay more attention to the distractor word.…”
Section: Discussionmentioning
confidence: 99%
“…These frequency effects are analogous to those seen in other types of conflict tasks, such as traditional Stroop or flanker tasks, in which the distracting information shares features with the target and so can create response conflict. In such tasks, performance improves when the proportion of conflict trials increases -an effect that has been attributed to increased cognitive control when conflicts are expected (Botvinick, Braver, Barch, Carter, & Cohen, 2001;Dishon-Berkovits & Algom, 2000; see reviews in Bugg, 2012;Bugg & Crump, 2012). The Dual Mechanisms of Control (DMC) model (Braver, 2012;Braver, Gray & Burgess, 2007;Braver, Paxton, Locke, & Barch, 2009) provides a useful framework in which to interpret the effect of distractor frequency on cognitive control.…”
Section: Cognitive Control Of Non-emotional Distractionmentioning
confidence: 99%